The cross-section measurement for the 3H(e, e′K+)nnΛ reaction. (6th December 2021) - Suzuki, K N; Gogami, T; Pandey, B; Itabashi, K; Nagao, S; Okuyama, K; Nakamura, S N; Tang, L; Abrams, D; Akiyama, T; Androic, D; Aniol, K; et al.
Abstract: The small binding energy of the hypertriton leads to predictions of the non-existence of bound hypernuclei for isotriplet three-body systems such as nn Λ. However, invariant mass spectroscopy at GSI has reported events that may be interpreted as the bound nn Λ state. The nn Λ state was sought by missing-mass spectroscopy via the ( e, e ′ K + ) reaction at Jefferson Lab's experimental Hall A. The present experiment has higher sensitivity to the nn Λ-state investigation in terms of better precision by a factor of about three. The analysis shown in this article focuses on the derivation of the reaction cross-section for the 3 H(γ*, K + )X reaction. Events that were detected in an acceptance, where a Monte Carlo simulation could reproduce the data well (|δ p/p| 4% ), were analyzed to minimize the systematic uncertainty. No significant structures were observed with the acceptance cuts, and the upper limits of the production cross-section of the nn Λ state were obtained to be 21 and 31 nb sr^-1 at the 90% confidence level when theoretical predictions of (− B Λ, Γ) = (0.25, 0.8) MeV and (0.55, 4.7) MeV, respectively, were assumed. The cross-section result provides valuable information for examining the existence of nn Λ.